Financial Recording Training for Food MSME in Pontianak Kemuning Market: Pelatihan Pencatatan Keuangan UMKM Pangan di Pasar Kemuning Pontianak - Pamela; Nurliza; Aditya Nugraha (Universitas Lancang Kuning, 2023)
Food MSME actors in traditional markets have limited capital so that the government helps MSMEs through the People's Business Credit (KUR) program. However, SMEs in traditional markets have another obstacle, namely the inability to make acceptable financial reports as the basis for providing credit or non-credit from banking institutions or other financial institutions. Financial records are important information for MSMEs such as cash in, cash out, accounts receivable, debt and others. Community service activities are to educate food MSMEs in recording financial transactions, and support government efforts to increase MSME capacity. So there is a need for Community Service Activities that will help improve MSME skills in terms of management, and finance. This community service activity is carried out by providing information through counseling, demonstrations, and technical guidance. This service activity is in the form of financial recording skills both manually and in applications. The results of this community service activity can help MSME actors to understand financial records both manually and by application.